Performance evaluation of next generation passive optical networks stage two for downstream transmission - Mahmood, Rawa Muayad (2017)
In this work, a 40 Gb/s downstream time and wavelength division multiplexing-passive optical network (TWDM-PON) for next-generation passive-optical-network second stage (NG-PON2) had been designed and demonstrated using VPI simulator. This work establishes simulation, analysis and performance evaluation of three different wavelength plans in TWDM-PON. TWDN-PON is selected as a primary solution to NG-PON2 in order to achieve and support the 40Gbit/s bandwidth requirement. A four 10-Gb/s TWDM-PON signals are stacked using four different wavelengths in the downstream direction and externally modulated. The three different wavelength plans have been simulated and evaluated so that the best plan can be selected in order to study the effect of distances and number of users. The downstream wavelengths for plan 1 and 3 range from 190.2 THz to 189.6 THz while for plan 2 the wavelengths range from 192.9 THz to 192.6 THz. Distance of 80 km and 100 km length with an optimum attenuation of 0.2 dB /km was employed to transfer the multiplexed signal. Based on the simulation results, the enhanced prototype system is able to support split ratio of 1:256 and 1:512. It can be concluded that for downstream transmission over 80 km and 100 km single mode fiber (SMF), plan 2 performs better than plan 1 and 3. Thus, plan 2 is further analyzed for transmission of triple play services which consist of voice, video and data.The system performance is observed using Bit Error Rate (BER) and Optical Signal-to-Noise Ratio (OSNR) with respect to the design parameters such as distance, number of users and received optical power. Thus, two different systems were implemented in term of number of supportable users, which are 256 users and 512 users, as well as the transmission distance that are 80 km and 100 km. When the system is tested upon transmission of triple-play services over 80km distance with 512 users, it is shown that BER of 8.9 × 10-10, 3.9 × 10-9 and 1.3 × 10-4 are achieved for data, voice and video, respectively.